Core outcome sets, developed collaboratively with patients, can improve the relevance and comparability of clinical trials. Issue 4 (3rd April 2023) - Mathioudakis, Alexander G.; Khaleva, Ekaterina; Fally, Markus; Williamson, Paula R.; Jensen, Jens-Ulrik; Felton, Tim W.; Brightling, Chris; Bush, Andrew; Winders, Tonya; Linnell, John; Ramiconi, Valeria; Coleman, Courtney; et al.
Properly designed and conducted randomised controlled trials (RCTs) represent the gold standard study type for conclusively evaluating any efficacy, effectiveness and/or safety of healthcare interventions. However, they are frequently associated with risks and burden to patients and require extensive resources [1]. These can only be considered acceptable if the RCTs fulfil their main objective, that is, to inform guidelines and clinical practice, and ultimately improve patients' health. Regrettably, RCTs are often less informative than they could be, owing to deficiencies in their design, and this may sometimes contribute to "research waste" [2, 3]. This needs to be remedied by strengthening and harmonising trial methods, delivery and reporting. This has implications across the breadth of clinical medicine. #RCTs in #Respiratory medicine require harmonisation. A core outcome set #COS is an agreed minimum set of outcomes that are critical for decision-making and should be evaluated in all future clinical trials. https://bit.ly/3XQmbtH